A Vulvovaginal Yeast Infection Caused by Cryptococcus victoriae in Vietnam: A Rare Case Report - Canh, Hoang Dinh; Loi, Cao Ba; Hung, Dao Nguyen; Van, Le Thi Hong; Quynh, Nguyen Thi Nhu; Dung, Do Thi Thuy; Tuan, Nguyen Ngoc; Anh, Do Ngoc (JIM - high impact case reports, 2024)
Cases of vulvovaginitis caused by Cryptococcus genus are exceedingly uncommon, with only a handful of instances having been described for this causative species. This report describes a rare case of vulvovaginitis suspected to be caused by Cryptococcus victoriae in a 58-year-old woman residing in an urban area of Hanoi city, Vietnam. The patient with a 10-year history of depression and type 2 diabetes mellitus was admitted to the hospital due to vulvar itching and vaginal discharge. Vaginal swabs confirmed the presence of a yeast infection by direct microscopic examination with 10% KOH and culture on CHROMagar Candida. The yeast was identified as C victoriae using genetic sequencing tools. The patient’s treatment plan involved topical clotrimazole and a daily oral dose of 200 mg of itraconazole for 7 days. This comprehensive treatment approach resulted in the patient’s full recovery. This is the first reported case of vulvovaginitis attributed to C victoriae in humans worldwide.